High resolution study of strongly interacting ν3(F2)/ν1(A1) bands of MSiH4 (M=28,29,30); Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 201 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Raspopova N. I. Natalya Ivanovna; Fomchenko A. L. Anna Leonidovna; Sydow C. Christian; Bauerecker S. Sigurd (2017, 2017)
Title screen